2011
DOI: 10.1371/journal.pone.0019283
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate Dose Escalation for the Treatment of Uncomplicated Malaria in a Region of Reported Artemisinin Resistance: A Randomized Clinical Trial

Abstract: BackgroundThe emergence of artemisinin resistance has raised concerns that the most potent antimalarial drug may be under threat. The currently recommended daily dose of artesunate (AS) is 4 mg/kg, and is administered for 3 days together with a partner antimalarial drug. This study investigated the impact of different AS doses on clinical and parasitological responses in malaria patients from an area of known artemisinin resistance in western Cambodia.MethodsAdult patients with uncomplicated P. falciparum mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 21 publications
1
83
0
Order By: Relevance
“…In our study, DHA IC 50 had low heritability, was significantly associated with no SNPs, and did not overlap with candidate SNPs associated with clinical parasite clearance phenotypes. These findings confirm that DHA IC 50 does not capture the delayed clearance phenotype that is the hallmark of artemisinin resistance in Cambodia (6)(7)(8) and emphasize the need to develop in vitro assays of artemisinin susceptibility that can be used for functional validation of candidate resistance genes.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In our study, DHA IC 50 had low heritability, was significantly associated with no SNPs, and did not overlap with candidate SNPs associated with clinical parasite clearance phenotypes. These findings confirm that DHA IC 50 does not capture the delayed clearance phenotype that is the hallmark of artemisinin resistance in Cambodia (6)(7)(8) and emphasize the need to develop in vitro assays of artemisinin susceptibility that can be used for functional validation of candidate resistance genes.…”
Section: Discussionmentioning
confidence: 65%
“…Extremely fast-acting, artemisinins kill both young ring forms and mature blood-stage parasites (3). The World Health Organization (WHO) recommended in 2001 that artemisinins be used strictly in combination therapies in hopes of delaying the emergence of resistance (2), but ACT treatment failure rates were rising on the Thailand/Cambodia border by 2006 (4,5) and progressively prolonged parasite clearance after treatment with artemisinin derivatives soon followed (6)(7)(8). This evidence that artemisinin resistance has emerged in western Cambodia, historically an epicenter of drug-resistant malaria, is an ominous development that threatens the recent major global investment in ACTs (3).…”
mentioning
confidence: 99%
“…Our incidental finding that the parasite clearance time of participants who received 6 mg/kg on Day 0 was significantly shorter than that of participants receiving the standard 4 mg/kg dose contrast with a recent study from Cambodia that found no change in clearance time or rate with higher artemisinin doses. 21 This observation, although based on small numbers, provides potentially important empirical evidence for the ability of higher artemisinin doses to hasten the parasite clearance of African isolates in the current stage of artemisinin usage on the continent.…”
Section: Discussionmentioning
confidence: 92%
“…artesunate is activated for the rest of intra-erythrocytic development, and thus, K13 variant parasites are fully susceptible to prolonged exposure to artemisinin, as clearly seen in vitro [2,4,5] and in vivo [3,22,23].…”
Section: Variants Of Pfk13 and The Parasite Cell Cycle In Vitromentioning
confidence: 95%
“…• P. falciparum harbouring variant K13 alleles, and/or demonstrating slow clearance at day 3, are clearly susceptible to extended-duration artemisinin-based treatment, as an ACPR of more than 90% has been achieved in the GMS with 6 days of artesunate monotherapy [23,24] or 3 days of artesunate monotherapy followed by 3 days of ACT [3]. Thus, regimens such as two sequential ACTs with different partner drugs have been postulated as a rational response to signs of falling 3-day ACT efficacy, and a protocol has been developed to evaluate such regimes before ACT failure becomes a serious problem [25].…”
Section: The Perceived Threat To Artemisinin-based Malaria Therapeuticsmentioning
confidence: 99%